Mitigation of DC and harmonic currents generated by voltage measurement errors and grid voltage distortions in transformerless grid-connected inverters - Trinh, Quoc Nam (2020)
The dc offset and scaling errors in the voltage measurements cause the injection of undesired dc and harmonic currents into the three-phase output currents of the grid-connected inverter. This study proposes an enhanced current control scheme to eliminate the dc and harmonic currents caused by voltage distortion and voltage measurement error in three-phase grid-connected inverters. The proposed current controller is designed in the synchronous (d-q ) reference frame and composed of a proportional resonant (PR) controller and a repetitive controller (RC). The role of the RC is to regulate the grid current follow the reference value as well as compensate all 6nωs and (6n±2)ωs(n= 1,2,3,⋯) harmonic components caused by distorted grid voltage and scaling errors. Meanwhile, the PR controller helps to compensate the dc current generated by dc offset measurement errors to guarantee that the three-phase grid currents are balanced and sinusoidal with extremely low dc component. Since the RC employed in the proposed current controller reduces to time delay by four times compared to the conventional RC, the proposed control system ensures good steady-state performance of the grid current without deteriorating its fast dynamic response. The effectiveness of the suggested solution is verified by various experimental tests.